Work Fatigue Among Apron Workers in the Mutiara Sis Al-Jufri Airport, Palu, Central Sulawes : Kelelahan Kerja Pada Pekerja Apron di Bandara Mutiara Sis Al-Jufri Palu Sulawesi Tengah - A. Ferina Herbourina Bonita; Amilah Eka Putri; Ummu Kamilah; Rendhar Putri Hilintang (Universitas Muhammadiyah Palu, 2025)
Fatigue has been reported to decrease the body's physical condition, work performance, and motivation. Previous studies revealed that working in the apron section of the airport with heavy work duration can cause tiredness. The common symptoms of fatigue include a low level of activity and motivation from various internal and external factors. Therefore, this study aims to determine the factors related to fatigue in apron workers. This is a quantitative and analytical observational study with a cross-sectional design. The sample population consists of 35 workers who were selected with the total sampling technique. The data obtained were analyzed with Univariate and Bivariate Analysis using a chi-square test. The results showed that a total of 1, 30, 3, and 1 respondents were in the very high, high, moderate, and low fatigue categories, accounting for 2.9%, 85.7%, 8.6%, and 2.9%, respectively. The results of the chi-square statistical test revealed that there was a relationship between age (p = 0.0026), length of work (p = 0.021), and gender (p = 0.000), while there was no significant association during work (p = 0.527). There was also no relationship between working period and work burnout among apron workers. Furthermore, airport authorities are advised to provide knowledge in the form of seminars or training on work fatigue to educate employees on how to overcome fatigue and the contributing factors. Apron workers must also rest and avoid forcing themselves to work during fatigue